2021
DOI: 10.1002/ardp.202100061
|View full text |Cite
|
Sign up to set email alerts
|

Phyllobilins as a challenging diverse natural product class: Exploration of pharmacological activities

Abstract: Phyllobilins are a group of chlorophyll‐derived bilin‐type linear tetrapyrroles, generated in the process of chlorophyll breakdown. Since the first phyllobilin was isolated and characterized in 1991, more and more structures of these chlorophyll catabolites were identified alongside the biochemical players involved in chlorophyll breakdown. In the meantime, phyllobilins are known to occur in a large natural structural variety, and new modifications are still being discovered. Phyllobilins have been regarded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Recent studies reported by Konícková et al have evaluated the possible anticancer effects of Spirulina platensis and Spirulina platensis-derived tetrapyrroles against pancreatic cancer cell lines (47). Furthermore, the phyllobilins are a group of chlorophyll-derived bilin-type linear tetrapyrroles with a significant potential in the anticancer treatment (48).…”
Section: Pyrrole -Pharmacology Profile and Anticancer Propertiesmentioning
confidence: 99%
“…Recent studies reported by Konícková et al have evaluated the possible anticancer effects of Spirulina platensis and Spirulina platensis-derived tetrapyrroles against pancreatic cancer cell lines (47). Furthermore, the phyllobilins are a group of chlorophyll-derived bilin-type linear tetrapyrroles with a significant potential in the anticancer treatment (48).…”
Section: Pyrrole -Pharmacology Profile and Anticancer Propertiesmentioning
confidence: 99%
“…Lifestyle change represents the first strategy to counteract the problem, although sometimes a pharmacotherapeutic approach is necessary. People also recourse to herbal products ignoring the real effectiveness and underestimating their safety profile 1 . In this context, the present work aimed at critically evaluating the efficacy and potential risk associated with weight loss botanicals.…”
Section: Ebook Of Abstractsmentioning
confidence: 99%
“…A careful evaluation of the risk/benefits profile of these supplements is necessary also considering they are often used as self-medication. References [1] Phyllobilins are a group of plant-derived bilin-type linear tetrapyrroles, which are generated in the process of chlorophyll degradation. Despite the visibility this biochemical pathway, the as well as the biochemical players involved have remained undetected for a very long time.…”
Section: Ebook Of Abstractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some gymnosperms and ferns like Pteridium aquilinum accumulate iso‐phyllobilanones, which present a major carbon‐skeleton rearrangement (Erhart et al, 2018; Schumacher et al, 2021). Given some phyllobilins are also bioactive compounds with antioxidative and anti‐inflammatory compounds (Wang et al, 2021), understanding the molecular basis of their synthesis and accumulation could bring interesting insight outside plant sciences toward potential pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%